Women Empowerment Through Self Help Groups - Kumar, Dr. Ajay (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Women continue to face issues from womb to the tomb. Over the past few years, the term financial inclusion has become nodal to Indian policy making. And still various attempts have been emerging to expand its scope. Financial inclusion can be explained as the delivery of banking services at low cost to the disadvantaged and low income groups. Financial inclusion covers financial services like credit, savings, insurance, payments, remittance, and so on. Nationalization of banks in 1969, multi-model approach of 1980, branch expansion, priority sector lending and so on paves the way for financial inclusion in India Keywords: Women empowerment, Financial, disadvantaged, Nationalization of banks